Highlights in BACE1 Inhibitors for Alzheimer's Disease Treatment - Coimbra, Judite R. M.; Marques, Daniela F. F.; Baptista, Salete J.; Pereira, Cláudia M. F.; Moreira, Paula I.; Dinis, Teresa C. P.; Santos, Armanda E.; Salvador, Jorge A. R. (Frontiers in Chemistry, 2018)
Alzheimer's Disease (AD) is a severe neurodegenerative disorder and the most common type of dementia in the elderly. The clinical symptoms of AD include a progressive loss of memory and impairment of cognitive functions interfering with daily life activities. The main neuropathological features consist in extracellular Amyloid-β (Aβ) plaque deposition and intracellular Neurofibrillary Tangles (NFTs) of hyperphosphorylated Tau. Understanding the pathophysiological mechanisms that underlie neurodegeneration in AD is essential for rational design of neuroprotective agents able to prevent disease progression. According to the “Amyloid Cascade Hypothesis” the critical molecular event in the pathogenesis of AD is the accumulation of Aβ neurotoxic oligomers. Since the proteolytic processing of Amyloid Precursor Protein (APP) by β-secretase (BACE1) is the rate-limiting step in the production of Aβ, this enzyme is considered a major therapeutic target and BACE1 inhibitors have the potential to be disease-modifying drugs for AD treatment. Therefore, intensive efforts to discover and develop inhibitors that can reach the brain and effectively inhibit BACE1 have been pursued by several groups worldwide. The aim of this review is to highlight the progress in the discovery of potent and selective small BACE1 inhibitors over the past decade.